THE PORTRAYAL OF WOMEN IN THE AWAKENING BY KATE CHOPIN - Mursalim, Raisa Murni Ananda; Rahman, Fathu; Amir P., M. (Universitas Hasanuddin, 2023)
This objective of this study is to explore Edna’s effort to deal with the perspective of Creole society in the Awakening Novel. This research used descriptive qualitative method in order to analyze the novel. In addition, the research applied the social perspective approach with the use of Berger’s theory. The result of this research shows that Creoles believe that women are feeble, should maintain silence, and submit to their husband's authority. Edna faces difficulties in her efforts to establish her Creole identity as a victim of discrimination, Edna gradually reveals her response to patriarchy and then Edna’s efforts is she defies Creole norms by falling in love with Robert Lebrun, sending her children to live with their grandmother, leaving her husband's home, and having an affair based solely on physical attraction with Alcee Arobin before committing suicide. Keywords: The Portrayal, Creola Society, Social Perspective, The Awakening.